Trace element concentration in mango (Mangifera indica L.), seedless guava (Psidium guajava L.) and papaya (Carica papaya L.) grown on agricultural and ex-mining lands of Bidor, Perak - L. H., Ang; L. T., Ng (Universiti Putra Malaysia Press, 2000)
Fruits namely mango, papaya, and seedless guava grown on agricultural and ex-mining lands in Bidor were sampled for analyse of heavy metal contamination. The concentration of mercury (Hg), lead (Pb), copper (Cu), zinc (Zn), nickel (Ni), arsenic (As) and cadmium (Cd) in the fruits were analysed. The results showed that, with the exception of Hg in mango and Pb in guava, fruits grown on agricultural land have higher levels of heavy metals than those grown on ex-mining land. The concentration of heavy metal in all fruits of both soil types ranged from 0.06 to 0.55 mg kgI for Cd, 0.02 to 0.78 mg kgI for Hg, 0.63 to 8.71 mg kgI for Pb, 5.20 to 12.22 mg kgI for Zn, and 2.01 to 5.74 mg kgI for Cu. Both Cr and Ni were not detected in papaya grown on mine spoils, whilst As was not detected in all fruits grown on both types of soils. The findings indicate that all fruits contained unacceptably high levels of Hg and Pb. The probable causes of contamination are discussed. Further studies are required to investigate the cause of heavy metal contamination in these fruits.